Lentivirus-Mediated Overexpression or Silencing of Aquaporin 1 Affects the Proliferation, Migration and Invasion of TNF-α-Stimulated Rheumatoid Arthritis Fibroblast-Like Synoviocytes by Wnt/β-Catenin Signaling Pathway - Zhou MY; Cai L; Feng XW; Mu YR; Meng B; Liu FY; Li R (Dove Medical Press, 2021)
Meng-yuan Zhou,1,* Li Cai,1,2,* Xiao-wen Feng,1 Yu-rong Mu,1 Bo Meng,1 Fang-yuan Liu,1 Rong Li1 1Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, School of Pharmacy, Anhui Medical University, Hefei, 230032, Anhui Province, People’s Republic of China; 2Department of Pathology, School of Basic Medicine, Anhui Medical University, Hefei, 230032, Anhui Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rong LiSchool of Pharmacy, Anhui Medical University, 81 Meishan Road, Hefei, 230032, Anhui Province, People’s Republic of ChinaTel +86 551-65172132Email aydlirong@163.comIntroduction: Previous studies have confirmed the pathologic role of synovial aquaporin 1 (AQP1) in rheumatoid arthritis (RA), but its associations with the abnormal biologic behaviors of fibroblast-like synoviocytes (FLS) remain unclear. Herein, we examined the roles of AQP1 in the proliferation, migration and invasion of TNF-α-stimulated RA FLS (MH7A cells) and explored the underlying mechanisms.Materials and Methods: Lentivirus-mediated AQP1 overexpression or silencing MH7A cells was constructed. Assays of MTT, flow cytometry (PI staining and Annexin V-PE/7-AAD staining), TMRM staining, wound-healing, transwell and phalloidin staining were performed to detect cell proliferation, cycle distribution, apoptosis, migration and invasion. The involvement of Wnt/β-catenin pathway was revealed by Western blot and β-catenin immunofluorescence staining.Results: AQP1 overexpression promoted cell proliferation of TNF-α-stimulated MH7A by facilitating transformation from G0/G1 to S phase and inhibiting cell apoptosis (ie, reduced apoptosis rates, raised mitochondrial membrane potential, increased Bcl-2 protein level and decreased levels of Bax and cleaved caspase 3 protein). Also, AQP1 overexpression increased the migration index as well as the numbers of migrated and invasive cells. Furthermore, AQP1 overexpression promoted the activation of Wnt/β-catenin pathway, and XAV939, an inhibitor of Wnt/β-catenin, canceled the above effects of AQP1 overexpression on MH7A cells. As expected, AQP1 silencing exhibited the opposite effects on TNF-α-stimulated MH7A cells, which could be reversed by LiCl, an activator of Wnt/β-catenin.Conclusion: AQP1 can affect the proliferation, migration and invasion of MH7A cells by Wnt/β-catenin signaling pathway, and AQP1 can be as a crucial determiner that can regulate RA FLS biologic behaviors.Keywords: aquaporin 1, rheumatoid arthritis, fibroblast-like synoviocytes, Wnt/β-catenin signaling pathway, biologic behaviors